The Influence of Parental Support and Self-Efficacy on Underprivileged Students Interest in Pursuing Higher Education - Faradina Qurrataayun; Neti Hernawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2026)
The high interest of underprivileged high school students in pursuing higher education is not always accompanied by their success in entering university, as they often face greater economic and social challenges, including financial constraints and limited parental support. This study aimed to examine the influence of parental support and self-efficacy on underprivileged students' interest in pursuing higher education. A quantitative approach with an explanatory research design was employed in this study, which was conducted at Master School Depok in May 2025. The participants consisted of 44 tenth-grade students and 26 eleventh-grade students who were selected purposively based on the criterion of having both parents living. Data were collected using a self-administered questionnaire. The results showed that the majority of underprivileged students were categorized as having moderate levels of parental support and self-efficacy. Meanwhile, their interest in pursuing higher education was categorized as low. The findings further revealed that self-efficacy was positively and significantly associated with and influenced students' interest in pursuing higher education. This indicates that higher levels of self-efficacy may contribute to a stronger interest in continuing education at the university level. However, parental support was not found to have a significant effect on students' interest in pursuing higher education. These findings highlight the importance of developing strategies and providing support from various sources to enhance the self-efficacy of underprivileged students, thereby fostering greater interest in pursuing higher education.